Implementasi literasi siswa melalui nilai-nilai Pancasila di Sekolah Dasar Negeri Jombang - Khoirun Nisa'; Wahyudi; Chusnul Chotimah (Indonesian Journal of Islamic Religious Education, 2024)
The moral literacy movement through Pancasila values is very important. Formal education institutions have an important role in efforts to instill Pancasila values through moral literacy to realize the goals of national education. This research focuses on 1) Planning of students' moral literacy through Pancasila values 2) Implementation of Pancasila values 3) Implication of students' moral literacy through Pancasila values. The purpose of this study is to describe literacy, Pancasila values and its implications for students of Jombang State Elementary School. This research used a qualitative approach. Data collection techniques were carried out by 1) interview, 2) documentation, 3) observation. Observation. Data analysis includes data reduction, data interpretation or data collection, presentation, data verification and conclusion drawing. The results of this study show that 1) Pancasila moral literacy planning includes several stages, namely: the habituation stage, the coaching stage, and the learning stage. 2) The values of Pancasila in Jombang State Elementary School include divine value, human value, unity value, populist value, and justice value. 3) The implication can realize the learning atmosphere and learning process to make more active students to develop their potential who have spiritual strength, religion, self-control, personality, intelligence, noble character, and skills needed for themselves, society, nation and state.